Similarity of Gramicidin S and Cryoprotectant Polyethylene Glycol Membranotropic Effects - Kalinovych, Viacheslav S.; Berest, Volodymyr P. (Problems of Cryobiology and Cryomedicine, 2019)
Probl Cryobiol Cryomed 2019; 29(2): 161.